(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
The present study focused on alleviating the issue of premature abscission of micro-shoots emerged from the cultured nodal segments in Kinnow mandarin. To resolve the problem, explants of different maturity stages, culture media, growth regulator combinations and ethylene inhibitors (silver compounds) were evaluated. Hardwood stage was observed to be the most efficient explant maturity stage to boost the vigorous early shoot emergence on MS (Murashige and Skoog) medium. Addition of GA3 (Gibberellic acid) 10 mg L−1 resulted in delayed abscission. Further reduction in abscission rate and healthy shoot growth were observed when subculturing of micro-shoots was done on MS medium supplemented with BAP 2.5 mg L−1, GA3 10 mg L−1 and silver thiosulfate 5 mg L−1. This modified procedure could be effectively utilized for mass multiplication as well as crop improvement in Kinnow mandarin.